2022
DOI: 10.1186/s12884-022-04505-5
|View full text |Cite
|
Sign up to set email alerts
|

Safety of SARS-CoV-2 vaccination during pregnancy- obstetric outcomes from a large cohort study

Abstract: Background COVID-19 during pregnancy is associated with adverse outcomes for mother and fetus. SARS-CoV-2 vaccination has significantly reduced the risk of symptomatic disease. Several small studies have reported the safety of SARS-CoV-2 vaccination during pregnancy, with no adverse effect on obstetric outcomes. Objective To examine the association between SARS-CoV-2 vaccination during pregnancy and maternal and neonatal outcomes in a large cohort … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 14 publications
(4 reference statements)
0
26
0
1
Order By: Relevance
“…These nine studies included 40 728 pregnant women, 21 297 (52.3%) of which received the COVID‐19 vaccine, while 19 431 (47.7%) pregnant women did not receive it. The majority of studies were performed in Israel 33–37 and the USA 38,39 ; one study was performed in Romania 40 and another in the UK 41 . Only two studies were prospective, 38,40 whereas the others were retrospective observational analyses.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These nine studies included 40 728 pregnant women, 21 297 (52.3%) of which received the COVID‐19 vaccine, while 19 431 (47.7%) pregnant women did not receive it. The majority of studies were performed in Israel 33–37 and the USA 38,39 ; one study was performed in Romania 40 and another in the UK 41 . Only two studies were prospective, 38,40 whereas the others were retrospective observational analyses.…”
Section: Resultsmentioning
confidence: 99%
“…This decision depends mainly on two reasons: first, there is heterogeneity among the included studies in what they reported, that is if the diabetes was gestational or pregestational, and in the way they reported, mainly in third trimester, so that it is difficult to prove that diabetes is a consequence of the vaccine, given that according to guidelines the diagnosis is made around 24–28 weeks at latest 46 . In detail, Dick et al, 34 Citu et al, 40 and Wainstock et al 37 describe only gestational diabetes mellitus but it is not specified whether it is diagnosed before or after the vaccine uptake; Beharier et al 33 and Rottenstreich et al 36 cumulate gestational and pregestational diabetes mellitus; Goldshtein et al, 35 Blakeway et al, 41 and Theiler et al 39 differentiate pregestational and gestational diabetes mellitus but the last is not mentioned in the subgroup analyses without COVID‐19‐affected pregnant women, so we took into consideration only the pregestational one.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They included a larger sample and explored the association between risk of preterm birth and vaccination in early, midterm and late pregnancy separately. They found a higher risk of preterm delivery in those who were vaccinated in the midterm of pregnancy (8.1% vs. 6.2%).We therefore hypothesized that unmeasured confounding factors associated with vaccination may have contributed to the results [19].…”
Section: Disscussionmentioning
confidence: 91%
“…As compared with individuals with uninfected pregnancies, infection with COVID‐19 during pregnancy increases the risk for preterm birth 2–4 and preterm birth via cesarean 3,5 ; premature rupture of membranes 5 ; lower neonatal Apgar score 5 ; venous thromboembolism 3 ; severe maternal morbidity 3 ; and maternal mortality 1,2 . Scientific evidence supporting the safety of the COVID‐19 vaccines during pregnancy continues to accumulate, with the evidence to date overwhelmingly suggesting the three COVID‐19 vaccines currently available in the United States are safe and effective during pregnancy, and that vaccination reduces the risk of adverse obstetric outcomes 6–21 . COVID‐19 vaccination during pregnancy, including the booster, also appears to provide passive protection and further protects the young infant 22–26 …”
Section: Introductionmentioning
confidence: 99%